Retroperitoneal Laparoscopic Radical Nephrectomy for Renal Cell Carcinoma: Indications and Long-term Outcome of a Cohort Study in Vietnam - Nguyen, Huy Hoang; Do, Truong Thanh; Hoang, Long; Do, Ngoc Son; Van, Tran Cam; Nguyen, Duc Minh (Open Access Macedonian Journal of Medical Sciences, 2022)
OBJECTIVE: Laparoscopic radical nephrectomy (LRN) has been suggested as the standard care for cancer patients in the T1-2 stage. However, whether this advanced technique is most indicated suitable for renal tumors higher than T3a and N1 is unclear, especially in different regions and countries, such as the difference between European and Asia. METHODS: From 2013 to 2021, the data of pathologically diagnosed renal cell carcinoma (RCC) patients who received laparoscopic retroperitoneal radical nephrectomy was subjected to the present study. RESULTS: Overall, all the registered Vietnamese patients were eligible for the study. The average operative time was 86.8 ± 21.2 min and the percentage number of patients in stages 1, 2, and 3 were 134 (70.2%), 30 (15.7%), and 27 (14.1%), respectively. Patients in the 3rd stage had a significantly longer operative time than stages 1–2 (p = 0.0001). No Lymph-node dissection (LND) was recorded in 10 patients (5.2%), limited LND in 163 patients (85.3%), regional LND in 13 patients (6.8%), extended LND (eLND) in 5 patients (2.6%). eLND showed only prolongation of operative time (p = 0.000), however, did not increase intraoperative complications as well as prolonged the duration of analgesia and hospital stay when compared with the other 2 groups (p = 0.82, 0.85, 0.91). Mean follow-up time: 42.3 ± 24.7 months. The 5-year recurrent free survival and 5-year overall survival of the stage 1, 2, 3 were: 98.3%, 100%, 87.8%, and 98.9%, 100%, and 91.3%, respectively. (p = 0.0011, p = 0.0082). CONCLUSION: Retroperitoneal LRN could be an important technique in improving long-term oncological outcomes for Vietnamese patients, especially in the stage of T1-3N0-1M0 tumors. Radical retroperitoneal nephrectomy is safe and technically feasible as well as providing favorable long-term oncological outcomes for stage T1-2-3aN1M0 RCC.